Experimental study on the low-velocity impact failure mechanism of foam core sandwich panels with shape memory alloy hybrid face-sheets - Li Hao (De Gruyter, 2021)
Superelastic shape memory alloy (SMA) as an advanced smart material has been used to improve the impact performance of fiber-reinforced composites in recent decades. Due to the low impact toughness of the thin composite face-sheet and the poor strength of the foam core, sandwich panels are sensitive to the transverse loading. SMA fibers were embedded into the composite laminated to improve the impact resistance of the traditional foam core sandwich panel in this work. Five new types of SMA hybrid panels were prepared, and the testing panels with penetration failure were observed at the impact energy of 50 J. The impact mechanical responses and the damage morphology were analyzed, and the impact failure mechanism was also revealed. Results show that all sandwich panels were failed, the fiber breakage occurred at the impact region in the traditional panels, while part plies of the rear face-sheets split-off in the SMA hybrid panels. The impact performance of the SMA hybrid panels is improved when compared with the traditional panel, the reduction of the delamination area by 48.15% and the increase of the load-bearing threshold by 32.75% are acquired for the hybrid sandwich panel with two layers of SMA fibers in the rear face-sheet.